NURSING CARE TO THE CHILD WITH CANCER: AN INTEGRATIVE REVIEW OF THE LITERATURE - Thiago Privado da Silva; Joséte Luzia Leite; Nereida Lucia Palko dos Santos; Ítalo Rodolfo Silva; Ana Carolina Abeid Mendonça; Maria José Carvalho Santos; Laura Johanson da Silva (Universidade Federal de Santa Maria, 2013)
http://dx.doi.org/10.5902/217976926918 Objective: to review the scientific production related to the nursing cares to the child with cancer. Method: bibliographic study, descriptive uses the integrative review method of the literature. The data was collect in January of 2013 utilizing as data's base Latin American and Caribbean Health Sciences Literature, Nursing Database and Bibliographic Index on Health Sciences from Spain, in accordance with the inclusion criteria previously established. Results: The final sample was constituted by ten studies. The nursing care to the child with cancer is investigated from many perspectives prevailing research in hospital setting. There was a predominance of descriptive, exploratory studies of qualitative approach. The studies underscore the need to put the family in nursing care plans. Conclusion: the study evidences the need of capacitation professional and psychological supporting to the nurse acting of this clientele and appreciation of the subjective aspects of care.